PSYCHOLOGICAL CONFLICTS OF ANNIE CHARACTER IN THE HORSE WHISPERER NOVEL WRITTEN BY NICHOLAS EVANS - LESTARI, KOLONA BUDI (LANTERN (Journal on English Language, Culture and Literature), 2015)
The purposes of this thesis are to analyze the intrinsic and extrinsic elements contained in The Horse Whisperer novel written by Nicholas Evans and to analyze the novel deeply using Psychological Theory of Id, Ego, and Superego by Sigmund Freud. The method used in the writing of this thesis is library research through internet browsing and reading books. Nicholas Evans’s The Horse Whisperer tells about the story of a woman who tries to heal her child and her horse suffering from trauma after having an accident. They both have burden of life and trauma that they face until they find a horse whisperer who does not only heal their horses but also their lives. From the analysis, the writer can conclude that Annie has Id, Ego and Superego in herself and she has to control it to get balance psychological life. The author shows several psychological aspects which make this novel become attractive.